Prediction Model of Mass Rapid Transit Noise Level Using the Stepwise Regression Analysis - Hamid N.B.; Sanik M.E.; Noor H.M.; Prasetijo J.; Mokhtar M.; Azmi M.A.M.; Yahaya M.I.; Ramli M.Z. (Springer Science and Business Media Deutschland GmbH, 2023)
Acoustic noise; Noise pollution; Rapid transit; Wind; Mass rapid transit; MRT train; Noise levels; Non-operating hour; Operating hours; Prediction modelling; Regression modelling; Sound level meter; Stepwise regression analysis; Regression analysis